GAMBARAN KONDISI KESEHATAN GIGI DAN MULUT PADA LANSIA DI BEBERAPA KOTA INDONESIA (Politeknik Kesehatan Kemenkes Bandung, 2020)
The elderly have a decline in their body’s resistance that makes them susceptible to diseases, include the oral disease. The condition of dental and oral health in elderly tends to be very bad and less attention, whereas oral health can affect general health and decrease their quality of life. This study study aims to get description of DMF-T and OHI-S index in elderly. This type of research is descriptive with literature study method, by studying and analyzing data obtained from journals, books, and other references. Based on the results of literature study, the mean score of DMF-T index of elderly in several cities of Indonesia is 17 on very high category. This score shows that every elderly have 17 missed, filled and decay teeth due to caries. OHI-S score with good criteria as many as 17 people (7,3%), 117 people showed moderate criteria (50,2%), and 99 people showed a bad criteria (42,5%). Therefore elderly people need to applying clean and healthy behavior pattern, especially in oral health to avoid illness and its severity of elderly. The conclusion of this study is DMF-T index in elderly has 17 mean score on very high category, with OHI-S score on moderate criteria. Key words: Dental and Oral Health, Elderly